2023
DOI: 10.31943/mathline.v8i1.378
|View full text |Cite
|
Sign up to set email alerts
|

Pocket Book Design Based On Mathematical Puzzles To Improve The Mathematical Logical Intelligence Of Grade XI Students

Abstract: Teachers have a big role in developing and improving students' mathematical logical intelligence skills. However, teachers only focus on using package books in teaching in the classroom. As a result, students do not show a great attitude of enthusiasm, students struggle and are unable to think logically, creatively and innovatively in developing skills when doing math problems. Therefore, researchers are interested in creating a pocket book based on Mathematical Puzzles (TTM) class XI. This study aims to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Based on the results of the content validity, construct validity, and graphic validity tests, it was found that each validity component item met the valid category. Content validity is carried out to ensure the accuracy of the sound wave material and to describe the learning content and learning objectives (Sirait et al, 2023). This is supported by Ginting et al (2023) that an instrument is said to be valid if it can measure what it wants to measure.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of the content validity, construct validity, and graphic validity tests, it was found that each validity component item met the valid category. Content validity is carried out to ensure the accuracy of the sound wave material and to describe the learning content and learning objectives (Sirait et al, 2023). This is supported by Ginting et al (2023) that an instrument is said to be valid if it can measure what it wants to measure.…”
Section: Resultsmentioning
confidence: 99%